Patient-reported burden of myasthenia gravis: baseline results of the international prospective, observational, longitudinal real-world digital study MyRealWorld-MG - Dewilde, Sarah; Philips, Glenn; Paci, Sandra; Beauchamp, Jon; Chiroli, Silvia; Quinn, Casey; Day, Laura; Larkin, Mark; Palace, Jacqueline; Berrih-Aknin, Sonia; Claeys, Kristl G; Muppidi, Srikanth; et al. (BMJ open, 2023)
ObjectivesMyasthenia gravis (MG) is a rare, chronic, autoimmune neuromuscular disease which can affect functional and mental aspects of health and health-related quality of life (HRQoL). This study aims to obtain detailed knowledge of the impact of MG on HRQoL in a broad population from the perspective of the patient.DesignProspective, observational, digital, longitudinal real-world study.SettingAdult patients with MG from seven countries (USA, Japan, Germany, UK, Italy, Spain and Canada) downloaded a mobile application onto their phones and entered data about themselves and their MG.Outcome measuresData was collected using the following general and disease-specific patient-reported outcome measurements: EuroQol 5 Domains Health-Related Quality of Life Questionnaire (EQ-5D-5L), Myasthenia Gravis Activities of Daily Living (MG-ADL), Myasthenia Gravis Quality of Life 15-item revised scale (MG-QoL-15r), Hospital Anxiety and Depression Scale (HADS) and Health Utilities Index III (HUI3). Patients were categorised by their self-assessed Myasthenia Gravis Foundation of America (MGFA) class (I–V).ResultsBaseline results of 841 participants (mean age 47 years, 70% women) are reported . The distribution across the MGFA classes was: 13.9%, 31.0%, 38.1%, 15.5% and 1.6% for classes I–V. The MGFA class was a strong predictor of all aspects of HRQoL, measured with disease-specific and with generic instruments. The domains in which patients with MG most frequently mentioned problems were usual activities, anxiety and depression, tiredness, breathing and vision. The mean total MG-ADL Score was positively associated with increasing MGFA classes: 2.7, 4.4, 6.3 and 8.4 for MGFA classes I–IV. Mean baseline EQ-5D-5L utility was also associated with MGFA classes and was 0.817, 0.766, 0.648 and 0.530 for MGFA class I–IV.ConclusionsMG has a large impact on key aspects of health and HRQoL. The impact of this disease increases substantially with increasing disease severity.